Strain Localization Parameters of AlCu4MgSi Processed by High-Energy Electron Beams; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Lunev A. G. Alexey Gennadievich; Nadezhkin M. V. Mikhail Vladimirovich; Konovalov S. V.; Teresov A. D. (2015, 2015)
Title screen